Effect of advanced glycation end products formed methylglyoxal, a food-borne dicarbonyl precursor, on the exacerbation of diabetic kidney disease by NOX4/Nrf2/NLRP3 inflammasome signaling pathway in db/db mice - Hee-Weon Lee; Min Ji Gu; Donghwan Kim; Eun Hee Han; Yoonsook Kim; Sang Keun Ha (Applied Biological Chemistry)
Abstract Western-style diets, which are abundant in advanced glycation end products (AGEs), particularly methylglyoxal-derived AGE4, have been identified as contributing factors to the progression of diabetic kidney disease. The objective of this study was to elucidate the pathogenic mechanisms of AGE4 in renal injury via the NOX4/Nrf2/NLRP3 inflammasome pathway. AGE4 was administered to diabetic db/db mice to evaluate renal histopathology, mitochondrial dysfunction, and oxidative stress. Concurrently, mouse tubular kidney proximal cells (TKPTS) were subjected to transfection with RAGE small interfering RNA (siRNA) and treatment with AGE4 to evaluate molecular alterations in vitro. Histological and functional deterioration of the kidney in db/db mice was observed following AGE4 exposure, accompanied by upregulation of NOX4 and RAGE, and disrupted mitochondrial integrity. Notably, AGE4 activated NLRP3 inflammasome components, including NLRP3, ASC, Caspase-1, and IL-1β, indicating enhanced inflammatory signaling. In vitro results confirmed these findings, showing that RAGE knockdown suppressed AGE4-induced NOX4/Nrf2/NLRP3 inflammasome activation and mitigated mitochondrial damage. These findings demonstrate that AGE4 promotes oxidative stress and inflammation through RAGE-mediated NOX4/Nrf2/NLRP3 inflammasome signaling, contributing to diabetic kidney disease pathogenesis. This study underscores a novel mechanism of AGE4-induced renal injury and emphasizes its potential as a therapeutic target in diabetic nephropathy.